2020
DOI: 10.1038/s41598-020-64990-6
|View full text |Cite
|
Sign up to set email alerts
|

Rapid pyritization in the presence of a sulfur/sulfate-reducing bacterial consortium

Abstract: Sedimentary pyrite (feS 2) is commonly thought to be a product of microbial sulfate reduction and hence may preserve biosignatures. However, proof that microorganisms are involved in pyrite formation is still lacking as only metastable iron sulfides are usually obtained in laboratory cultures. Here we show the rapid formation of large pyrite spherules through the sulfidation of Fe(III)-phosphate (FP) in the presence of a consortium of sulfur-and sulfate-reducing bacteria (SRB), Desulfovibrio and Sulfurospirill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 83 publications
2
48
2
Order By: Relevance
“…Although pyrite was only detected in the sediments and not in the water column, sulfate-rich enrichment cultures from this lake led to rapid pyrite formation after 21 days of culture (Berg et al, 2020). Here, our results demonstrate that the sole activity of Desulfovibrio (representing 80 % of the microbial consortium in the enrichment (Berg et al, 2020)) was able to promote pyrite formation. However, while, in the present study, pyrites occurred as infra micrometric spherules undetectable by X-ray diffraction after one month, pyrites produced within the Lake Pavin consortium were visible on diffractograms after only 21 days and occurred as beads of 1 µm in diameter (Berg et al, 2020).…”
Section: Environmental Implicationsmentioning
confidence: 55%
See 4 more Smart Citations
“…Although pyrite was only detected in the sediments and not in the water column, sulfate-rich enrichment cultures from this lake led to rapid pyrite formation after 21 days of culture (Berg et al, 2020). Here, our results demonstrate that the sole activity of Desulfovibrio (representing 80 % of the microbial consortium in the enrichment (Berg et al, 2020)) was able to promote pyrite formation. However, while, in the present study, pyrites occurred as infra micrometric spherules undetectable by X-ray diffraction after one month, pyrites produced within the Lake Pavin consortium were visible on diffractograms after only 21 days and occurred as beads of 1 µm in diameter (Berg et al, 2020).…”
Section: Environmental Implicationsmentioning
confidence: 55%
“…The results of the present study demonstrate that Desulfovibrio desulfuricans alone had the ability to induce vivianite formation in the FP-nano condition, suggesting that sulfatereducing bacteria could play a significant role in vivianite formation in natural environments. Despite a low sulfate concentration (<20 µM), Lake Pavin hosts a plethora of sulfate-reducing bacteria in its water column (Lehours et al, 2005;Berg et al, 2019;Berg et al, 2020) and pyrite was found abundantly in the first 12 cm of its sediments, in association with abundant vivianite (Viollier et al, 1997;Busigny et al, 2014;Busigny et al, 2016). Although pyrite was only detected in the sediments and not in the water column, sulfate-rich enrichment cultures from this lake led to rapid pyrite formation after 21 days of culture (Berg et al, 2020).…”
Section: Environmental Implicationsmentioning
confidence: 93%
See 3 more Smart Citations